(Z)-3-(4-Chlorophenyl)-2-{[N-(2-formylphenyl)-4-methylbenzenesulfonamido]methyl}prop-2-enenitrile - Madhanraj, R. (International Union of Crystallography, 2011)
In the title compound, C24H19ClN2O3S, the sulfonyl-bound benzene ring forms dihedral angles of 38.1 (2) and 81.2 (1)°, respectively, with the formyl benzene and benzene rings. The molecular conformation is stabilized by a weak intramolecular C—H⋯O hydrogen bond, which generates an S(5) ring motif. The crystal packing is stabilized by C—H⋯O hydrogen bonds, which generate C(7) zigzag chains along [010] and R 3 3(19) ring motifs along [010]. The crystal packing is further stabilized by C—Cl⋯π interactions [Cl⋯centroid = 3.456 (2) Å and C—Cl⋯centroid = 173.4 (2)°].